Accuracy of computational fluid dynamics indices of unruptured cerebral aneurysms with 3 T magnetic resonance angiography. - Mori, Futoshi; Saito, Mikito; Fujimoto, Kentaro; Kubo, Yoshitaka; Koji, Takahiro; Akamatsu, Yosuke; Ogasawara, Kuniaki; Matsuda, Tsuyoshi; Uwano, Ikuko; Yamashita, Fumio; Tanaka, Ryoichi; Sasaki, Makoto (Neuroradiology, 2025)
Purpose: Computational fluid dynamics (CFD) analysis has been applied to predict the rupture of cerebral aneurysms, and results suggest that wall shear stress (WSS) and related metrics can be imaging markers for the risk of rupture. Computed tomography angiography (CTA) is commonly used as source images for CFD analyses. However, it remains unknown whether less-invasive magnetic resonance angiography (MRA) can be used as a substitute for CTA. Hence, we investigated if CFD metrics calculated from MRA were comparable to those calculated from CTA in cerebral aneurysms. Methods: Sixty-three patients with 86 unruptured aneurysms who underwent MRA at 3T and CTA were retrospectively enrolled between 2012 and 2018 from a prospective cohort study. We performed CFD analyses to obtain indices including the WSS, WSS gradient (WSSG), and oscillatory shear index (OSI) of aneurysmal walls and compared these values between MRA and CTA. Results: Statistically significant correlations and agreements were observed between MRA and CTA for the mean/minimum WSS, mean/minimum WSSG, and maximum OSI values (correlation coefficient = 0.60–0.79, intraclass correlation coefficient = 0.62–0.79). However, the mean OSI value exhibited suboptimal correlation and agreement (0.48 and 0.31, respectively). Multivariate regression analyses further revealed significant negative correlations between discrepancies in the mean WSS/WSSG between MRA and CTA and the aneurysm angle. Conclusion: Except for the mean OSI, CFD values of unruptured cerebral aneurysms obtained from 3T MRA showed good correlations and agreements with those from CTA, indicating that 3T MRA can be partly applied for CFD analyses of cerebral aneurysms.